Perfluorododecanoic acid exposure induced developmental neurotoxicity in zebrafish embryos. (October 2018) - Guo, Xiaochun; Zhang, Shengnan; Lu, Shaoyong; Zheng, Binghui; Xie, Ping; Chen, Jun; Li, Guangyu; Liu, Chunsheng; Wu, Qin; Cheng, Houcheng; Sang, Nan
Abstract: Perfluorododecanoic acid (PFDoA), an artificial perfluorochemical, has been widely distributed in different ambient media and has been reported to have the potential to cause developmental neurotoxicity. However, the specific mechanism is largely unknown. In the current study, zebrafish embryos were treated with 0, 0.24, 1.2, and 6 mg/L PFDoA for 120 h. Exposure to PFDoA causes serious decreases in hatching delay, body length, as well as decreased locomotor speed in zebrafish larvae. Additionally, the acetylcholine (ACh) content as well as acetylcholinesterase (AChE) activity were determined to be significantly downregulated in PFDoA treatment groups. The level of dopamine was upregulated significantly after treating with 1.2 and 6 mg/L of PFDoA. Gene expressions related to the nervous system development were also analyzed, with the exception of the gene mesencephalic astrocyte-derived neurotrophic factor ( manf ), which is upregulated in the 6 mg/L treatment group. All other genes were significantly downregulated in larvae in the PFDoA group in different degrees. In general, the results demonstrated that PFDoA exposure could result in the disruption of the cholinergic system, dopaminergic signaling, and the central nervous system. Graphical abstract: Image 1 Highlights: PFDoA altered motor behaviors in zebrafish larvae. PFDoA decreased neuron-specific GFP expression in Tg (HuC-GFP) zebrafish larvae. The alternation of neurotransmitters levels indicated the developmental neurotoxicity induced by PFDoA in zebrafish larvae. PFDoA inhibited cholinergic system and neuronal development and altered expressions of related genes. Abstract : PFDoA resulted in hypoactivity and inhibition of AChE enzymes, as well as alternation of related genes in the early developmental stages of zebraﬁsh, causing developmental neurotoxicity.